Diagnosis and treatment of solid pseudopapillary neoplasm of the pancreas in children: A report of 18 cases - Ayiguzaili Maimaijiang; Haiyun Wang; Wanfu Li; Yaqi Wang (Frontiers in Pediatrics, 2022)
PurposeTo explore the incidence, imaging and treatment of solid pseudopapillary tumor of pancreas in children, and Summarize the experience of treatment.MethodsThe clinical data of 18 children with a solid pseudopapillary tumor of the pancreas treated in our hospital from January 2012 to June 2021 were analyzed retrospectively. The age range was 8–16 years old, the average age was 11.67 years old, and the median age was 11.5 years old, namely, three boys with an average age of 10 years old and 15 girls with an average age of 12 years old. In total, two cases were admitted to the hospital because of trauma, seven cases were found in physical examination, and nine cases were admitted with the abdominal pain as the main complaint. Enhanced CT examination was performed before operation, nuclear magnetic resonance examination and abdominal ultrasound examination were performed in some children, and plain CT scan was performed after operation.ResultsSolid pseudopapillary tumor of the pancreas can occur in all parts of the pancreas, especially in the body and tail of the pancreas. Among the 18 cases, SPN occurred in the head of pancreas in 5 cases (27.78%), the neck of pancreas in 2 cases (11.11%), and the body and tail of pancreas in 11 cases (61.11%). All the 18 children were treated by operation. among them, 4 cases underwent choledochal pancreatico duodenectomy (1 case), 4 cases underwent pancreaticoduodenectomy combined with splenectomy (3 cases), 6 cases underwent spleen-preserving pancreatectomy / tail pancreatectomy (1 case), 3 cases underwent enucleation of pancreatic tumor due to exogenous growth, 1 case underwent laparoscopic partial pancreatectomy and pancreaticoenterostomy. Laparotomy was performed in 12 cases and endoscopic surgery in 6 cases. Postoperative pathology confirmed solid pseudopapillary tumor of the pancreas. None of the patients received radiotherapy and chemotherapy after operation and were followed up for 6 months to 2 years. There was no recurrence, metastasis or pancreatic dysfunction.ConclusionSolid pseudopapillary tumor of pancreas in children is a rare, low-grade malignant solid tumor with no specific clinical manifestations and laboratory examinations. Preoperative diagnosis mainly depends on enhanced CT. Surgical resection of tumor is a reliable treatment, and the specific operation is mainly based on the experience of the chief surgeon, the location of the tumor and the invasion of surrounding tissue. At present, there is no evidence of the effectiveness of other treatment options, and surgical resection of the tumor has a good prognosis.